Role of Laser in Oral and Maxillofacial Surgery: A Review of Literature - Tiwari, Arunesh Kumar; -, Balram; Kumar, Sunit; Tripathi, Rashmi (Journal of Orofacial Research, 2015)
Lasers have been used in dentistry for diagnostic and therapeutic purposes for more than 30 years, and are an indispensable instrument in any modern dental surgery. The use of lasers enables new treatment methods to be employed in order to meaningfully supplement traditional therapies. The purpose of this paper is to overview the use of laser as use widely. In this paper, we are summarized the role of laser in different oral and maxillofacial disease by review of literatures. Oral and maxillofacial surgery is a vast branch of dentistry which includes procedures ranging from simple extraction to pathologies of both the hard and soft-tissues. Based on extensive review of literature, certain conclusion can be made regarding the use of lasers